FT-IR ANALYSIS AND ANTI BACTERIAL ACTIVITY OF SILK SERICIN - J.DIVYA; DR.J.SRINIVASAN; B.GEETHA MANOHARI (International Journal of Pharma and Bio Sciences, 2016)
Realization of current trends and innovative uses of insect fiber, silk is required to exploit its compatibility, eco friendly and value addition potential. An adhesive silk protein sericin has high potential for use in biomedical applications. It has important properties such as excellent oxygen permeability, cell protecting and antioxidant action, moisture regulating ability, protection from ultraviolet (UV) radiation and microbes, wound healing, anticancer and anticoagulant properties. Hence this study was taken to find out the bioactive functional groups present in silk extract of Sericin for their antibacterial activity. The characterization and presence of functional groups in sericin was achieved by Fourier Transform Infrared Spectroscopy (FT-IR) analysis. Antibacterial activity of silk extract of sericin was evaluated against two pathogenic bacterial species, namely gram negative bacterial pathogen Escherichia coli and gram positive bacterial pathogen Staphylococcus aureus by agar well diffusion method. The FT-IR analysis revealed the presence of functional groups such as primary amine, carboxylic acid, alkane, aromatic ring and alcohol. Major peaks were observed at 3425.58 and 1064.71 cm-1 which corresponds to N-H and O-H functional groups respectively. Both pathogenic bacterial species were sensitive to silk extract of sericin. For the treatment of diseases associated with these pathogenic bacteria the silk extract of sericin have promising antibacterial potential and could be effective natural medicine.